An Investigation into the Effect of Problem-based Learning on Learners' Writing Performance, Critical and Creative Thinking Skills - Helaluddin Helaluddin; Misnah Mannahali; Duwi Purwati; Alamsyah Alamsyah; Hengki Wijaya (National Research University Higher School of Economics, 2023)
Research Background: In addition to mastering writing skills, students must also be able to develop critical and creative thinking skills. These two skills play an important role so that students can survive and compete in the world of work in the era of the industrial revolution 4.0. The gap in Knowledge and Purpose of the Study: Although there have been many experimental studies using problem-based learning in learning to write, the existing research is still inadequate in exploring the impact of this model on writing performance and critical and creative thinking skills. Method: This study uses a sequential mix-method design that combines quantitative and qualitative data collection and analysis techniques. The participants of this study were students from the Islamic Banking Study Program at UIN Sultan Maulana Hasanuddin Banten, as many as 61 people. Data were collected using questionnaires, essay writing tests, assessment rubrics, and interviews. Quantitative data were analyzed using SPSS 25.00 by running paired sample t-tests and one-way ANCOVA. In addition, data from semi-structured interviews were analyzed qualitatively using thematic analysis techniques. Findings and Value Added: research findings state that PBL positively influences writing performance and critical and creative thinking skills. The interviews showed that the students had positive attitudes and perceptions towards using the PBL method in learning to write to improve these three skills. The findings of this study are expected to increase knowledge about how students can improve writing performance, critical thinking, and creative thinking. In addition, it is also hoped that these findings can be an alternative in choosing writing learning methods.